PQRST (Preview, Question, Read, State, Test) Method’s Effectiveness towards Reading Comprehension of Analytical Exposition Text at SMAN 1 Katibung - Syifa Nurfadhila; Mutiara Ayu (Edumaspul: Jurnal Pendidikan, 2025)
This study aims to analyze the effectiveness of the PQRST method in improving students' reading comprehension of analytical exposition texts. The research design employs a quantitative approach with a quasi-experimental design involving two groups: the experimental group, which was taught using the PQRST method, and the control group, which received passive instruction through direct teacher explanations. Data were collected through a reading comprehension test to measure students' understanding. The Independent Sample T-test result indicates significant differences between the experimental and control groups' post-test scores. The two-tailed significance (Sig) value was 0.000, which is lower than the significance level of α = 0.050, confirming a statistically significant difference between the two groups. The experimental group, which applied the PQRST method, scored higher than the control group. Based on these findings, it can be concluded that the PQRST method significantly enhances students' reading comprehension of analytical exposition texts.